Antifungal Properties of Biosurfactant Produced by Bacterial Strains SR17 and JS29 Against Phytopathogens of Rubber - Mena, Sushmita; Deka, Suresh (International Journal of Scientific Research in Biological Sciences, 2020)
Biosurfactants are microbial metabolites synthesized by certain microorganisms, yeast, and fungi. They possess characteristic features showing physiological properties especially antifungal and antibacterial behaviour. Among all derivatives of glycolipid particularly the species Pseudomonas that contains rhamnose biosurfactants proves to have the highest potential in inhibiting the flourishing range of phytopathogens. The practical examples of spraying of pesticides and fertilizers in the agricultural fields result in a hazardous impact in plant growth hence the application of biosurfactants have a promising future in different aspects of sustainable agriculture because of being biodegradable and cost effective. The paper focused on the inhibition by biosurfactants obtained from Pseudomonas aeruginosa SR17, Pseudomonas aeruginosa JS29, Bacillus altitudinis MS16 and V1 strain (not yet identified) against the rapid growth of phytopathogenic fungal cultures. In the initial stage, the inhibitory impact of Cell Free Supernatant (CFS) of each bacterial strains were homogenized with Potato Dextrose Agar (PDA) for analyzing upon phytopathogens. Later, the crude biosurfactant is extracted from centrifuged CFS at temperature 40°C under reduced pressure. Authors narrated that a 500mg/l concentration of crude is incorporated with PDA and analyzed for the inhibition. Paper concludes two noble strains SR17 and JS29, which demonstrate an average inhibition of 57% and 63% respectively. Biosurfactants of these two peculiar strains can be used effectively in the prevention of disease.